COVID-19 in A Liver Cirrhosis Patient - Sasmithae, Lia (The Indonesian Society for Digestive Endoscopy, 2022)
The COVID-19 pandemic is a novel disease and posed a great challenge in the current healthcare system. The exact impact of the COVID-19 virus on the liver is still unknown. However, in a patient with chronic liver disease, most COVID-19 infections will affect the survival rate and initiate liver decompensation. This study reported a 50-years-old man who complained about bloody vomit and black tarry stool with COVID-19 infection. Physical examination findings included hematemesis, pale conjunctiva, ascites, collateral vein; and from the rectal toucher, there was melena. There was no fever, cough, or shortness of breath. The laboratory and radiological examinations showed that there were normochromic normocytic anemia, hypoalbuminemia, slightly increased ALT/AST, HBsAg (+), and abdominal ultrasound findings were liver cirrhosis with ascites. The patient was screened for the COVID-19 antigen swab test (+), further confirmed by the COVID-19 PCR swab test (+). The treatment given for hematemesis and melena was Gastric Cooling; the patient was fasted, then received somatostatin PPI drip, Vitamin K injection, PRC transfusion, lactulose, ceftriaxone, ascites fluid puncture, and albumin transfusion. After the bleeding resolved, the patient received spironolactone and propranolol. The treatments for COVID-19 were Azithromycin, Favivirapir, Vitamin D, Vitamin K, and Zinc. The patient was hospitalized for 11 days and then improved. Conclusion: This study reported a case of a 50 years-old man with ruptured esophageal varices due to liver cirrhosis with concomitant COVID-19 infection and improved with comprehensive therapy despite the limited facilities at the hospital.